2021
DOI: 10.1021/acs.jpcc.1c02264
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Exchange of Atomically Precise Nanoclusters with Materials of Varying Dimensions: From Nanoscale to Bulk

Abstract: We present isotopic exchange reactions of atomically precise silver nanoclusters (NCs) with materials of different dimensions, namely, NCs, plasmonic nanoparticles (NPs), and bulk metals, all made of silver. Isotopically pure 109Ag25(DMBT)18 – and 107Ag25(DMBT)18 – (DMBT is 2,4-dimethyl benzene thiol) were reacted with Ag NPs of different sizes in the range of ∼2–11 nm, protected with the same ligand. The exchange of 107Ag/109Ag atoms in the NC was monitored using electrospray ionization mass spectrometry. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Recently, Chakraborty et al reported the dynamics of isotopic exchange reactions of isoto-pically pure Ag nanocluster with different dimensions of metallic Ag, like nanoclusters, plasmonic NPs, and bulk. 289 Isotopically pure 107 Ag 25 (DMBT) 18 and 108 Ag 25 (DMBT) 18 was reacted with different sizes of Ag@DMBT NPs (naturally abundant Ag). With the increase in the NP size, the rate of atomic exchange was reduced.…”
Section: Interparticle Reactions: Reactions With Higher Dimension Mat...mentioning
confidence: 99%
“…Recently, Chakraborty et al reported the dynamics of isotopic exchange reactions of isoto-pically pure Ag nanocluster with different dimensions of metallic Ag, like nanoclusters, plasmonic NPs, and bulk. 289 Isotopically pure 107 Ag 25 (DMBT) 18 and 108 Ag 25 (DMBT) 18 was reacted with different sizes of Ag@DMBT NPs (naturally abundant Ag). With the increase in the NP size, the rate of atomic exchange was reduced.…”
Section: Interparticle Reactions: Reactions With Higher Dimension Mat...mentioning
confidence: 99%
“…NP−NC reactions are spontaneous and stoichiometric in nature. 52,71 Figure 3B shows the time-dependent evolution of the mass spectral features of [Ag 25 (DMBT) 18 ] − NC upon interaction with Au NP (full range MS in Figure S7). As the reaction progressed, the peak corresponding to the parent species, [Ag 25 (DMBT) 18 ] − NC (m/z 5166), gradually shifted toward a higher mass species, [Ag 24 Au(DMBT) 18 ] − NC (m/z 5255), NC (m/z 5344) was also observed at a reasonable intensity (isotopic distribution patterns in Figure S8).…”
Section: Interparticle Reaction At Structurally and Compositionally A...mentioning
confidence: 99%
“…72 A later study on the kinetics of isotopic exchanges showed a size dependence when the reacting partner was varied from the nanoscale to bulk metal with an isotopically pure [Ag 25 (SR) 18 ] − NC. 52 A recent study showed [Ag 25 (SR) 18 ] − NC-meditated site-selective etching of anisotropic Au nanotriangles (Au NTs). 73 ] − and CuO NP reaction, which induced the aggregation of Cu-doped NC leading to spherical superstructures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the size- and framework-maintained metal exchange occurs in the reaction of [Ag 25 (DMBT) 18 ] − with [Au 25 (PET) 18 ] − , 14 [Ag 7 (H){S 2 P(O i Pr) 2 } 6 ] with [Cu 7 (H){S 2 P(O i Pr) 2 } 6 ], 15 and the isotopic exchange reactions of [ 107/109 Ag 25 (DMBT) 18 ] − (ref. 16 ) and [ 107/109 Ag 29 (BDT) 12 (TPP) 4 3− ]. 17 Of note, the inter-cluster reactions between two structurally distinct clusters have also been reported.…”
Section: Introductionmentioning
confidence: 99%